THE EFFECT OF PRICE DISCOUNTS ON PURCHASING DECISIONS AT CITI MART STORE IN GUNUNGSITOLI CITY - Juni Kristiani Zega; Serniati Zebua; Yupiter Mendrofa; Idarni Harefa (LPPM YPITI, 2026)
Thdiscounts, purchasing decisions, marketing strategiesis study aims to determine and analyze the effect of price discounts on purchasing decisions for Morinaga products at Citi Mart Stores in Gunungsitoli City. The background of this study is based on the phenomenon of high consumer interest in Morinaga products when price discounts are applied, which shows the importance of price promotion strategies in increasing purchasing decisions. The research method used is a descriptive quantitative approach with data collection techniques through questionnaires distributed to 60 consumer respondents who have purchased Morinaga products at Citi Mart Stores during the promotional period. Data were analyzed using validity tests, reliability, simple linear regression, coefficient of determination, and t-tests with the help of the SPSS version 26 program. The results showed that price discounts had a positive and significant effect on purchasing decisions with a significance value of 0.018 (<0.05), a coefficient of determination of 9.2%, and a relationship level of 0.304 which is included in the sufficient category. This indicates that even though the influence is relatively small, price discounts still have a role in influencing consumer purchasing decisions, while there is the possibility that other factors are more dominant in influencing purchasing decisions, such as product quality, brand preferences, or consumer psychological factors. Thus, a discount strategy can be an effective promotional alternative, but it needs to be combined with other marketing factors to be more optimal in attracting consumer purchasing interest.